THE CONCEPT OF "PROPERTY", "PROPERTY RIGHTS" AND THEIR RELATION TO THE CATEGORIES OF "PROPERTY" AND "OWNERSHIP" - Nauryzbayev , Айбек Динмухамедович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2013)
This article analyzes the concept of "property" as the object of civil law in comparison with the concepts of "property rights", "property" and "ownership".